Novel Hamy Mean Aggregation Operators Based on Advanced Operations for T-Spherical Fuzzy Group Decision-Making - Wang, Haolun; Zhao, Wei; Liu, Jiang; Feng, Liangqing; Mahmood, Tahir; Kumar, Kamal (Journal of Intelligent Decision Making and Information Science, 2025)
Some advanced operation laws (AdOLs) are put forward with the T-spherical fuzzy (TSF) information. A series of novel Hamy mean aggregation operators are developed, specifically TSF advanced Hamy mean (TSFAdHM), TSF advanced dual Hamy mean (TSFAdDHM), TSF advanced weighted Hamy mean (TSFAdWHM) and TSF advanced weighted dual Hamy mean (TSFAdWDHM) operators. These aggregation operators integrate the strengths of Hamy mean and AdOLs in that they not only reveal correlations among multi-input variables but also eliminate counter-intuitive problems, as well as reflect decision-maker risk preferences. Several reasonable natures and peculiar types of these aggregation operators are investigated. Moreover, a novel group decision-making framework for the type of TSF aggregation operator is constructed. The tractability and usefulness of the decision-making model are examined by some numerical examples. The sensitivity and method comparison analyses are used to demonstrate that the proposed model can remedy the drawbacks of existing methods, and this article offers a very useful method for the complicated group decision-making issues.